2021
DOI: 10.1590/1678-4685-gmb-2020-0461
|View full text |Cite
|
Sign up to set email alerts
|

Periostin regulates osteogenesis of mesenchymal stem cells from ovariectomized rats through actions on the ILK/Akt/GSK-3β Axis

Abstract: Osteoporosis is a condition of the skeleton that mainly results from estrogen deficiency. Periostin is a matricellular component in bone that is involved in osteoblast differentiation. However, how Periostin promotes osteogenesis remains largely unknown. Here, we isolated bone marrow skeletal stem cells (BMSCs) derived from an ovariectomy (OVX)-induced osteoporosis rat model and the effects of periostin on BMSCs derived from OVX rats (OVX-BMSCs) were assessed. Overexpression of periostin enhanced alkaline phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(39 reference statements)
2
3
0
Order By: Relevance
“…Mesenchymal stem cells can differentiate into osteoblasts, 39 whereas hematopoietic stem cells can differentiate into macrophages and osteoclasts 40 . Previous studies found that periostin promoted the migration and osteogenic differentiation of mesenchymal stem cells 41,42 . Our study showed consistent results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mesenchymal stem cells can differentiate into osteoblasts, 39 whereas hematopoietic stem cells can differentiate into macrophages and osteoclasts 40 . Previous studies found that periostin promoted the migration and osteogenic differentiation of mesenchymal stem cells 41,42 . Our study showed consistent results.…”
Section: Discussionsupporting
confidence: 89%
“…40 Previous studies found that periostin promoted the migration and osteogenic differentiation of mesenchymal stem cells. 41,42 Our study showed consistent results. Periostin was downregulated during the differentiation of MC3T3-E1 cells in vitro and decreased in Prrx1+ osteoprogenitors during bone defect repair after terbutaline treatment.…”
Section: Discussionsupporting
confidence: 85%
“…It changes 3-phosphoglycerate (3-PG) to 2- phosphoglycerate (2-PG) 20 1 40.6 0.001352 16.85 UBC_MOUSE Polyubiquitin C Polyubiquitin C is a ubiquitin protein and involved in protein modification (ubiquitination) # 5 42.2 0.000019 14.46 TPIS_MOUSE Triosephosphate isomerase Triosephosphate isomerase is an efficient glycolytic enzyme in cartilage metabolism by catalyzing glycerone phosphate or dihydroxyacetone phosphate (DHAP) and D-glyceraldehyde-3-phosphate (GA3P) 21 1 48.8 0.010625 12.99 COCA1_MOUSE Procollagen, type XII, alpha 1 Procollagen12a1 is involved in col12a1 formation, which is a minor collagen in the extracellular matrix of articular cartilage 22 3 23.8 0.000083 12.17 COAA1_MOUSE Collagen-alpha-1 type X Collagen10a1 or collagen X is the extracellular matrix which exclusively synthesized by hypertrophic chondrocytes and found in the calcified zone of articular cartilage 22 2,3 18.5 0.000838 11.68 RAB1A_MOUSE Rab1A Rab1A is a small GTPase and recruits mTORC1 under amino acid simulation at the Golgi 23 . mTORC1 regulates chondrocyte proliferation and differentiation 24 1,2 10.7 0.000002 11.50 POSTN_MOUSE Periostin Periostin is an extracellular matrix protein and coordinates cell adhesion and differentiation 25 . It has been identified as a g...…”
Section: Resultsmentioning
confidence: 99%
“…Periostin mainly triggers signaling pathways such as NF-KB/STAT3, P13K/Akt and focal adhesion kinase (FAK) by binding to cell surface integrin receptors αvβ3 and αvβ5, and regulates the expression of downstream genes. It plays an important role in adhesion, tissue repairing and maintaining the integrity of connective tissue structure and function [72].…”
Section: Periostinmentioning
confidence: 99%